Cultural Heritage Identity of Informal Settlements Based on The Social Construction Culture: A Conceptual Framework - Firmansyah, Aldrin Yusuf (Proceedings of the International Conference on Green Technology; Vol 14 No 1 (2024): Proceeding of 14th International Conference on Green Technology, 2025)
The purpose of this research is to conceptualize cultural heritage as a common identity in the form of urban informal settlements in the form of kampung especially Kayutangan village, Malang city, which until now has not received attention or been studied, especially related to minority stereotypes in marginalized local communities. The identity of informal settlements is in a dynamic-spontaneous identity polarization position as a negotiation of the history of marginalization and oppression, and on the other hand it is still trapped in a static condition of only enriching city artefacts without the involvement of the community. As a common identity, it means that cultural heritage is considered important by multi-stakeholders, both residents and external parties. The form of shelter as a form of cultural artifact is the result of social construction related to its technological culture, and its ability to become a common identity if there is intercultural awareness among its stakeholders. The research method uses literature studies over the last 10 years in bibliometric format. The bibliometric method is a quantitative method for analyzing bibliographic data contained in articles or journals. This analysis uses computer assistance to scientifically review publications related to a particular topic or field. The research results play a role in assembling a variety of related thoughts, and reviewing cultural heritage more broadly to strengthen identity, cultural diversity and shared cultural rights, as a common identity